A mathematical model of white blood cell dynamics during maintenance therapy of childhood acute lymphoblastic leukemia - Le, Thuy T.T.; Jost, Felix; Raupach, Thomas; Zierk, Jakob; Rauh, Manfred; Suttorp, Meinolf; Stanulla, Martin; Metzler, Markus; Sager, Sebastian (Mathematical Medicine and Biology, 2019)
Acute lymphoblastic leukemia is the most common malignancy in childhood and requires prolonged oral maintenance chemotherapy to prevent disease relapse after remission induction with intensive intravenous chemotherapy. In maintenance therapy, drug doses of 6-mercaptopurine (6-MP) and methotrexate (MTX) are adjusted to achieve sustained antileukemic activity without excessive myelosuppression. However, uncertainty exists regarding timing and extent of drug dose responses and optimal dose adaptation strategies. We propose a novel comprehensive mathematical model for 6-MP and MTX pharmacokinetics, pharmacodynamics and myelosuppression in acute lymphoblastic maintenance therapy. We personalize and cross-validate the mathematical model using clinical data and propose a real-time algorithm to predict chemotherapy responses with a clinical decision support system as a potential future application.
CRIS-Team Scopus Importer:2019-12-24
Keywords: chemotherapy; childhood acute lymphoblastic leukemia; maintenance therapy; ordinary differential equations; parameter estimation; real-time algorithm

Corrigendum to: “Resistance to antibacterial therapy in pediatric febrile urinary tract infectionsda single-center analysis” [J Pediatr Urol 16 (2020) 71–79] (Journal of Pediatric Urology (2020) 16(1) (71–79), (S1477513119303389), (10.1016/j.jpurol.2019.10.018)) - Raupach, Thomas; Held, Jürgen; Prokosch, Hans-Ulrich; Rascher, Wolfgang; Zierk, Jakob (Journal of Pediatric Urology, 2022)
In order to fulfil the requirements of the doctoral office of the Friedrich-Alexander-University Erlangan-Nuremberg (FAU), the following updates have been made to the abovementioned article: Affiliation ‘a’ now reads as: Department of Pediatrics and Adolescent Medicine, Friedrich-Alexander-University Erlangen-Nuremberg (FAU), Erlangen, Germany. The following has been added to the Acknowledgements: The present work was performed in fulfilment of the requirements for obtaining the degree “Dr. med. (Doctor medicinae) at the Friedrich-Alexander University Erlangen-Nuremberg (FAU)”.
CRIS-Team Scopus Importer:2024-12-16

High-resolution label-free mapping of murine kidney vasculature by raster-scanning optoacoustic mesoscopy: an ex vivo study - Goebel, Colin A.; Brown, Emma; Fahlbusch, Fabian; Wagner, Alexandra; Buehler, Adrian; Raupach, Thomas; Hohmann, Martin; Späth, Moritz; Burton, Neal; Wölfle, Joachim; Schmidt, Michael; Hartner, Andrea; et al. (Molecular and Cellular Pediatrics, 2022)
Background: Chronic kidney disease (CKD) is a global burden affecting both children and adults. Novel imaging modalities hold great promise to visualize and quantify structural, functional, and molecular organ damage. The aim of the study was to visualize and quantify murine renal vasculature using label-free raster scanning optoacoustic mesoscopy (RSOM) in explanted organs from mice with renal injury. Material and methods: For the experiments, freshly bisected kidneys of alpha 8 integrin knock-out (KO) and wildtype mice (WT) were used. A total of n=7 female (n=4 KO, n=3 WT) and n=6 male animals (n=2 KO, n=4 WT) aged 6 weeks were examined with RSOM optoacoustic imaging systems (RSOM Explorer P50 at SWL 532nm and/or ms-P50 imaging system at 532 nm, 555 nm, 579 nm, and 606 nm). Images were reconstructed using a dedicated software, analyzed for size and vascular area and compared to standard histologic sections. Results: RSOM enabled mapping of murine kidney size and vascular area, revealing differences between kidney sizes of male (m) and female (f) mice (merged frequencies (MF) f vs. m: 52.42±6.24 mm2 vs. 69.18±15.96 mm2, p=0.0156) and absolute vascular area (MF f vs. m: 35.67±4.22 mm2 vs. 49.07±13.48 mm2, p=0.0036). Without respect to sex, the absolute kidney area was found to be smaller in knock-out (KO) than in wildtype (WT) mice (WT vs. KO: MF: p=0.0255) and showed a similar trend for the relative vessel area (WT vs. KO: MF p=0.0031). Also the absolute vessel areas of KO compared to WT were found significantly different (MF p=0.0089). A significant decrease in absolute vessel area was found in KO compared to WT male mice (MF WT vs. KO: 54.37±9.35 mm2 vs. 34.93±13.82 mm2, p=0.0232). In addition, multispectral RSOM allowed visualization of oxygenated and deoxygenated parenchymal regions by spectral unmixing. Conclusion: This study demonstrates the capability of RSOM for label-free visualization of differences in vascular morphology in ex vivo murine renal tissue at high resolution. Due to its scalability optoacoustic imaging provides an emerging modality with potential for further preclinical and clinical imaging applications.
CRIS-Team Scopus Importer:2022-07-15
Keywords: Chronic kidney disease; Ex vivo kidney imaging; msRSOM; Optoacoustic; Photoacoustic; Raster scanning optoacoustic mesoscopy; RSOM

Model-Based Simulation of Maintenance Therapy of Childhood Acute Lymphoblastic Leukemia - Jost, Felix; Zierk, Jakob; Le, Thuy T.T.; Raupach, Thomas; Rauh, Manfred; Suttorp, Meinolf; Stanulla, Martin; Metzler, Markus; Sager, Sebastian (Frontiers in Physiology, 2020)
Acute lymphoblastic leukemia is the most common malignancy in childhood. Successful treatment requires initial high-intensity chemotherapy, followed by low-intensity oral maintenance therapy with oral 6-mercaptopurine (6MP) and methotrexate (MTX) until 2–3 years after disease onset. However, intra- and inter-individual variability in the pharmacokinetics (PK) and pharmacodynamics (PD) of 6MP and MTX make it challenging to balance the desired antileukemic effects with undesired excessive myelosuppression during maintenance therapy. A model to simulate the dynamics of different cell types, especially neutrophils, would be a valuable contribution to improving treatment protocols (6MP and MTX dosing regimens) and a further step to understanding the heterogeneity in treatment efficacy and toxicity. We applied and modified a recently developed semi-mechanistic PK/PD model to neutrophils and analyzed their behavior using a non-linear mixed-effects modeling approach and clinical data obtained from 116 patients. The PK model of 6MP influenced the accuracy of absolute neutrophil count (ANC) predictions, whereas the PD effect of MTX did not. Predictions based on ANC were more accurate than those based on white blood cell counts. Using the new cross-validated mathematical model, simulations of different treatment protocols showed a linear dose-effect relationship and reduced ANC variability for constant dosages. Advanced modeling allows the identification of optimized control criteria and the weighting of specific influencing factors for protocol design and individually adapted therapy to exploit the optimal effect of maintenance therapy on survival.
CRIS-Team Scopus Importer:2020-04-14
Keywords: 6-mercaptopurine; childhood acute lymphoblastic leukemia; maintenance therapy; methotrexate; neutropenia; non-linear mixed-effects modeling; population pharmacokinetics/pharmacodynamics

Resistance to antibacterial therapy in pediatric febrile urinary tract infections—a single-center analysis - Raupach, Thomas; Held, Jürgen; Prokosch, Hans-Ulrich; Rascher, Wolfgang; Zierk, Jakob (Journal of Pediatric Urology, 2019)
Background: Febrile urinary tract infections (UTIs) are common serious bacterial infections in childhood and require early diagnosis and antibacterial therapy. However, considerable uncertainty exists regarding the optimal antibacterial agent for primary treatment of pediatric UTIs. Additionally, patterns of susceptibility and resistance change over time and microbiological in vitro resistance is not necessarily associated with treatment failure. Here, we analyzed uropathogens, their resistance patterns, and response to antibacterial treatment in children with acute pyelonephritis. Methods: We used billing codes (international classification of diseases) to identify all inpatients aged 0–18 years with febrile UTIs in a German university tertiary care center from 2009 until 2018. Microbial results were retrieved from the laboratory information system for all children, and treatment regimen and treatment response were analyzed in a subgroup of children. Results: We identified 907 children with acute pyelonephritis; in 590 cases (65%) an uropathogen was detected. Escherichia coli (60.8%), Enterococcus faecalis (13.2%), Klebsiella pneumoniae (7.0%), Proteus spp. (5.2%), and Pseudomonas aeruginosa (4.2%) were the most common pathogens. 353 of 436 E. coli isolates (81.0%) were susceptible or intermediate to aminopenicillin/β-lactamase-inhibitor (BLI) combinations. We examined 52 cases where E. coli was resistant to initial therapy with aminopenicillin/BLI combinations: Therapy was changed in 35 cases (67%) and left unchanged in 17 cases (33%), and we found no significant differences in C-reactive protein and leucocyte count in blood and urine between both groups after 3 days. Conclusions: We present the spectrum of uropathogens and susceptibility test results in pediatric UTIs in a tertiary care center. Our findings suggest a satisfactory response to first-line therapy with aminopenicillin/BLI combinations.
CRIS-Team Scopus Importer:2019-12-03
Keywords: Antibiotic susceptibility/resistance; Escherichia coli; Febrile urinary tract infections; Pediatrics